What Do Plastic Surgery Patients Think of Financial Conflicts of Interest and the Sunshine Act?. Issue 6 (June 2019) - Lopez, Joseph; Naved, Bilal A.; Pradeep, Tejus; Pineault, Kevin; Purvis, Taylor; Macmillan, Alexandra; Slezak, Sheri; May, James W.; Dorafshar, Amir H.
Abstract : Background: The purpose of this study was to evaluate patients' views of conflicts of interest (COI) and their comprehension of recent legislation known as the Physician Payments Sunshine Act. This report constitutes the first evaluation of plastic surgery patients' views on COI and the government-mandated Sunshine Act. Methods: This cross-sectional study invited patients at an academic, general plastic surgery outpatient clinic to complete an anonymous survey. The survey contained 25 questions that assessed respondents' perceptions of physician COI and awareness of the Sunshine Act. Analyses were performed to examine whether perspectives on COI and the Sunshine Act varied by level of education or age. Results: A total of 361 individuals completed the survey (90% response rate). More than half of respondents with an opinion believed that COI would affect their physician's clinical decision-making (n = 152, 52.9%). Although almost three fourths (n = 196, 71.2%) believed that COI should be regulated and COI information reported to a government agency, the majority were not aware of the Sunshine Act before this survey (n = 277, 81.2%) and had never accessed the database (n = 327, 95.9%). More than half of patients (n = 161, 59.2%) stated that they would access a publicly available database with physicians' COI information. A larger proportion of older and educated patients believed that regulation of physicians' COI was important ( P < 0.001). Conclusions: Awareness of and access to plastic surgeon COI information is low among plastic surgery patients. Older and more educated patients believed that transparency regarding COI is important with regard to their clinical care.